ANALISIS PENGARUH KINERJA FINANSIAL TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL PEMODERASI - Dita Murpradana (Jurnal Akuntansi Bisnis, 2015)
This study intends to determine the role of CSR disclosure variables in moderating influence on the value of the company's financial performance. Financial performance is measured in terms of ROA is believed to be the core variables that directly affect the value of the company, while CSR indirect effect through interaction with the financial performance as the moderating variable. Data analysis methods used to solve problems in this study is the use of test interaction is often called the Moderated Regression Analysis (MRA). This analysis is used to find and get a picture of the effect of Financial Performance (KF) against the value of the Company (NP) with CSR as moderating variables. Based on the hypothesis testing that has been done, the result that influence the value of Financial Performance Company with disclosure of Corporate Social Responsibility (CSR) as a moderating variable. So it can be proved that the disclosure of CSR was able to significantly moderate the relationship between the financial performance of the company's value.